Pengaruh Aglomerasi Industri, Angkatan Kerja dan Human Capital Investment Terhadap Pertumbuhan Ekonomi di Kawasan Regional Sumbagsel Ditinjau dari Perspektif Ekonomi Islam: Analisis Data Panel : Tahun 2017-2023 - Annisa Putri Lestari; Budimansyah; Yulistia Devi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the impact of agglomeration, labor force, and Human Capital Investment on economic growth in the Sumbagsel Regional Area. The research employs a quantitative approach. The concentration of industries that shapes consumption patterns influences the economic development of the surrounding areas, with the labor force supporting the economy to enhance production factors. Lastly, Human Capital Investment (HCI) refers to a field with sufficient human resources in terms of skills, knowledge, and health that can support economic growth. The data for this research was obtained from secondary sources using literature review and documentation methods for data collection. The analysis technique used is panel data regression testing with Eviews 12. The results indicate that simultaneously, Industrial Agglomeration (X1), Labor Force (X2), and Human Capital Investment (X3) have a positive and significant effect on economic growth (Y). The findings show that agglomeration, labor force, and human capital investment collectively influence economic growth in the Sumbagsel Regional Area.